Physical activity and persons with intellectual disability: some considerations for Latin America Actividad física en personas con discapacidad intelectual: algunas consideraciones para América Latina - Viviene A Temple; Heidi I Stanish (Salud Pública de México, 2008)
Physical activity is a personal and societal investment in health. In Latin America, rates of non-communicable diseases are growing and there is burgeoning interest in physical activity as a preventative health measure. This paper describes physical activity among adults with intellectual disability from a public health perspective; and provides recommendations related to the need for, and measurement of, physical activity among persons with intellectual disability in Latin America. La actividad física es una inversión en salud, tanto personal como social. En América Latina las tasas de enfermedades no transmisibles van en aumento y existe un creciente interés en la actividad física como medida de salud preventiva. Este artículo describe la actividad física entre adultos con discapacidad intelectual desde la perspectiva de la salud pública y proporciona recomendaciones pertinentes a la necesidad y medición de la actividad física entre personas con discapacidad intelectual en América Latina.